Technical report: determining the best ratio of dose per application for radiotherapy treatment by using Gompertz model / Norhashila Hashim, Nur Fartina Rezali and Rasyidah Ahmad - Hashim, Norhashila; Rezali, Nur Fartina; Ahmad, Rasyidah (2017)
Tumour are groups of abnormal cells that form lumps or growth. For this project, it focuses on breast tumour in determining the number of breast tumour cells after radiotherapy treatment. Gompertz model is used to measure the number of tumour cells based on the ratio of dose per application after radiotherapy treatment. The result from this project will show the best ratio of dose per application to the radiotherapy treatment for the fixed days which is 30 days.